Dynamics Simulation Analysis for the Escapement Mechanism of the Mechanical Watch Movement - Chen Shijia; Chen Lin; Gong Xiang (Jixie chuandong)
The escapement mechanism is considered to be the crucial component in a mechanical watch with a complicated motion. A dynamics model of the escapement mechanism is established based on the continuous impact force model,the dynamics simulation and calculation are carried out by using ADAMS. The results show that the dynamics response of each part under different input moment of escapement wheel can be directly predicted by the model,and therefore the corresponding instantaneous daily rate is calculated. Compared with the experimental data,the simulated results are able to predict the trend of the instantaneous daily rates in different driving torques in a moderate precision level. The model could be used to improve the performance of the escapement mechanism in the future.